Fundaments of agricultural sustainability or the quest for the Golden Fleece - Janssens, Marc; Gaese, Hartmut; Keutgen, Norbert; Ortega, Rodrigo; Torrico, Juan Carlos; Pohlan, Juergen (JNRD - Journal of Natural Resources and Development, 2014)
In this paper, different aspects of development sustainability will be highlighted by stressing the fact that even the smartest drivers are necessarily characterized by the continuous uncertainty we all must live with. Different development drivers will be illustrated in the field of agriculture, nature and environment, all attempting to weigh the contradicting, even conflicting parameters of life and decay. Agricultural sustainability drivers will encompass human, cultural, social and political aspects together with components of metabolism, genetics, energy, environment and farm management. It will be concluded that each sustainability approach should be precisely documented using exact parameters and not unproven social or emotional attributes. Quantitative cost to benefit ratios will be proposed as sustainability indicators. In short, sustainability is an ideal state in the area of conflict between environmental change, evolution of life and thermodynamic laws. It cannot be defined as a stable state, but as a state of relative stability during a certain but limited period of time. Sustainability strongly depends on a reliable energy resource that, in thermodynamic terms, enables the preservation of order in an open (eco-) system at the expense of the order of the environment.